"My Mother Is Dead": A Story of the Negative Mother Complex in Life and in Death. (2nd January 2019) - Kirst, Pamela Freundl
Abstract : Shortly after my mother died, I had a dream that prompted the exploration that became this article. In the dream, a gothic horror-film version of my dying mother forbade me to write about our relationship. In an effort to claim myself—to separate from the clutches of this negative archetypal force—and to understand the impact of her death, this work was born. The article considers the tensions in my relationship with my personal as well as the archetypal mother, recounts some of the events that took place as my mother lay ill, and records and contemplates the difficulty of a mourning process following the death of a parent with whom one has had a complicated relationship. Theoretical undergirding is also offered. The personal and theoretical material is presented in hopes that it will prove helpful for analyzing patients contending with difficult mothers, as well as for individuals who themselves grapple with tenacious mother issues.